A Model for Preventing Domestic Violence Using an Early Warning System in Criminal Law Policy - Hendro Widodo (Nusantara: Journal of Law Studies, 2026)
Indonesia, as a law-based country that upholds the supremacy of law and the protection of human rights, considers domestic violence a constitutional violation with widespread physical, psychological, and social consequences. The prevalence of domestic violence continues to increase, driven by power imbalances, economic vulnerability, and entrenched patriarchal culture, which demonstrates that repressive legal measures alone are insufficient to address the problem effectively. This study aims to develop a preventive criminal law policy model based on an early warning system to detect risks of domestic violence at an early stage, integrate cross-institutional data, and enable timely interventions before escalation. This research employs a normative or doctrinal legal methodology, analyzing statutory provisions, judicial decisions, doctrinal literature, and principles of Islamic and comparative criminal law. The study identifies that an effective preventive approach requires a systemic, integrated framework that combines early detection instruments with the strengthening of family functions and multi-stakeholder collaboration. Such a framework facilitates education, awareness, and coordinated interventions at institutional and community levels to protect victims and disrupt cycles of violence. The findings demonstrate that the proposed model emphasizes proactive, participatory, and risk-based strategies, integrating legal, social, and familial dimensions. Its novelty lies in the formulation of a comprehensive domestic violence prevention model that bridges early warning mechanisms with family resilience programs and collaborative stakeholder networks. This approach not only provides a preventive legal tool but also contributes to the development of holistic criminal law policies that prioritize victim protection, social empowerment, and sustainable reduction of domestic violence. Academically, this study contributes to the field of criminal law by providing a conceptual and operational framework for preventive justice, expanding the discourse on early intervention mechanisms, and bridging doctrinal legal studies with practical, multidimensional prevention strategies.